The plasma and cerebrospinal fluid pharmacokinetics of the platinum analog satraplatin after intravenous administration in non-human primates - Marcus, Leigh (Cancer Chemother Pharmacol, 2011)
BACKGROUND: Satraplatin is an orally bioavailable platinum analog with preclinical activity in cisplatin resistant models and clinical activity in adults with refractory cancers. The cerebrospinal fluid (CSF) penetration of cisplatin and carboplatin in non-human primates (NHP) is limited (3.7 and 2.6%, respectively). We evaluated the plasma and CSF pharmacokinetics (PK) of satraplatin after an intravenous (IV) dose in NHP. METHODS: Satraplatin (120 mg/m(2)) was administered as 1 h IV infusion in DMSO (5%) and normal saline to 5 NHP. Serial blood and CSF samples were obtained over 48 h. Plasma ultrafiltrate (UF) was immediately prepared by centrifugation. Platinum was quantified in plasma UF and CSF using a validated atomic absorption spectroscopy assay with lower limit of quantification (LLQ) of 0.025 μM in UF and 0.006 μM after concentration in CSF. Pharmacokinetic parameters were estimated using non-compartmental analyses. CSF penetration was calculated from the CSF AUC0–48h : plasma UF AUC0–48h. RESULTS: Satraplatin was well tolerated. Median (range) PK parameters in plasma UF were: maximum concentration (C(max)) 8.3 μM (5.7–10.6), area under the curve (AUC(0–48h)) 29.2 μM h (22.6–33.2), clearance 0.36 l/h/kg (0.31–0.37), and t(1/2) 18.8 h (13.4–25). Satraplatin was detected in the CSF of all NHP. Median (range) PK parameters in CSF were: C(max) 0.07 μM (0.02–0.12), AUC(0–48h) 1.2 μM h (0.49–2.43). The median (range) CSF penetration of satraplatin was 4.3% (2.2–7.4). CONCLUSIONS: Satraplatin penetration into CSF is similar to that of carboplatin and cisplatin, despite its greater lipophilicity. The development of a phase I trial of satraplatin for refractory childhood solid tumors including brain tumors is in progress.